The Role of History Education in National Development: A Jos Case Study - Vongdip, Stephen Hosea; Agai, Jock Matthew (Innovare Journal of Education, 2025)
History is a study of the past and the subject is vital for many reasons, including the careful collection, the preservation, and the creation of consciousness about the past that can guide towards the present and the future. The subject suffered a blow in the Nigerian curriculum because of its regular exclusion and inclusion by various administrations in the country. Another challenge that the subject of History suffers is that the indigenous peoples of Nigeria have not been writing their own histories; instead, other people write their histories for them. These researchers encourage Nigerians to begin to write their own histories. The research focuses on the importance of History as a subject to national development. The study employed a qualitative methodology is qualitative and this is necessary in order to obtain results on the perceptions of Nigerian students and teachers on the subject of teaching History in Nigerian schools. A case of two private schools in Jos has been collated. The study found a strong correlation between history education and national development. The researchers recommended that there is a need to revamp the curriculum of History in Nigeria with a view to emphasizing its roles towards national development.